Diagnostic utility and validation of a newly developed real time loop mediated isothermal amplification method for the detection of SARS CoV-2 infection - Bushran N Iqbal; Shiyamalee Arunasalam; Maduja V M Divarathna; AAOM Jabeer; PDNN Sirisena; Thamarasi Senaratne; Rohitha Muthugala; Faseeha Noordeen (Journal of Clinical Virology Plus, 2022)
Background: Detecting SARS-CoV-2 using a simple real time molecular assay will be helpful for the mitigation efforts in low / middle income countries during the pandemic. We have developed and validated a rapid and simple real time loop mediated isothermal amplification assay (LAMP) for screening of SARS-CoV-2 infection in known infected and non-infected individuals. Methods: Six sets of primers were designed targeting the N-gene of the SARS-CoV-2 (Accession ID MN994468). LAMP reactions were performed using Warm Start 2X Master Mix and real-time PCR machine at 65 °C for 60 cycles with 15 s for each cycle. Results were read by visualizing turbidity under ultraviolet light and real time fluorescence detection through FAM channel of the real time PCR machine. We tested a total of 320 including 240 SARS CoV-2 positive (Ct values <40) and 80 SARS CoV-2 negative samples as tested by a real time RT-PCR using the newly developed LAMP assay. Results: A total of 206 out of 240 SARS CoV-2 positive samples were tested positive by the newly developed LAMP assay with a sensitivity of 86%. All 80 SARS CoV-2 negative samples were tested negative by the newly developed LAMP assay with a specificity of 100%. Conclusion: The newly developed real time LAMP assay has a sensitivity of 86% and specificity of 100% compared to the real time RT-PCR for the detection of SARS CoV-2. The new assay will be useful to screen large number of samples if adopted to minimize the time and cost.